Mechanistic aspects of the radiation-chemical reduction of graphene oxide to graphene-like materials. (June 2014) - Flyunt, Roman; Knolle, Wolfgang; Kahnt, Axel; Prager, Andrea; Lotnyk, Andriy; Malig, Jenny; Guldi, Dirk; Abel, Bernd
Abstract Purpose: The aim of the work was to investigate mechanistic details of the preparation of graphene-like materials (GLM) via reduction of graphene oxide (GO) in aqueous dispersions by electron beam (EB) generated reducing free radicals. Materials and methods: A 10 MeV linear accelerator was employed to irradiate aqueous GO dispersions at ambient temperatures. The kinetics of GO reduction was followed using UV-Vis spectroscopy. The resulting GLM were characterized by X-ray photoelectron spectroscopy (XPS), Transmission electron microscopy (TEM), Raman spectroscopy and conductivity measurements. Results: The reduction of GO could be afforded with high efficiency within minutes at room temperature via the reaction of GO with reducing radicals generated by EB irradiation. The detailed investigation of the reduction mechanism allowed a selection of the best reducing free radicals in terms of both their efficiency and environmental impact of their precursors and final products. Conclusions: The EB-treatment of aqueous GO dispersions is a highly efficient, environmentally friendly, cost-effective and easily up-scalable method for the preparation of GLM. The efficiency of the new reduction approach is comparable with the best existing methods.